Die Südbahn Ihre Kurorte und Hotels - Vasko-Juhász, Désirée (2006)
The present manuscript is intended to be part I of a publication in two volumes, which deals with the historic architecture in the region of "Semmering" in southern Lower Austria from the point of view of art history, cultural history and history of architecture. The study was attempted in continuation of the FWF-project P 13959 under scientifical direction and supervision of the applicant (Prof.Dr. Mario Schwarz). Main topic of this study is the role and importance of the "Suedbahngesellschaft" (Southern Railway Company) in the process of the formation of the Semmering-region as a first-rate holiday resort of the Viennese society during the late 19th century up to the beginning of World War I. The study shows that the forming of this region mainly depended on the initiative of Friedrich Schueler, the Southern Railways Company's director, and Franz Schoenthaler, sculptor in duty of the Imperial Court. The materialization of the planning in the field of hotel-architecture in the first phase was due to architect Franz Wilhelm - collaborator of Wilhelm Flattich, who designed the railway-station of the Southern Railway Company at Vienna, in the second phase due to the architects Alfred Wildhack and Robert v. Morpurgo. The author's research brought a lot of new insight in work and biographies of these architects, who have been neglected so far by the art history. New, important results were achieved by this study concerning the links between the Semmering hotel-architecture and the grand hotel-resorts at Dobiacco (Toblach; architect: Wilhelm Flattich) and Opatija (Abbazia; architect: Alfred Wildhack e.a.), built by the Southern Railway Company as well, which have to be seen as activities in sense of the company's "corporate identity". Thus the company appears among the leading entrepreneurs in the world as founder of railway-hotels. The author presents several famous examples of this kind of hotels from Great Britain to the USA. Here the study is entering a field of architectural research, which still stands at the beginning. There are also important relations between the Semmering hotel-architecture and the historical hotels of Switzerland. In a large panorama the author includes the Semmering hotels in the general regional development of the "Wiener Hausberge" (hills and mountains near Vienna) during the second half of 19th century, especially in the time after the construction of the Semmering railway. The study comprehensively is illustrated with photographs of the object's exteriors and the interiors, historic views, plans and comparative illustrations. At the beginning of this volume, an introductory chapter, written by the applicant (Prof.Dr.Mario Schwarz), refers on new studies to the phenomenon of landscape aesthetification in view of the construction of the Semmering railway. The main topic is the factor of sensual apperception of the landscape during the continuous movement of a railway-ride and its genial exploitation by the railway's architects. This motivation has to be seen as climax and terminus of a development, which derived from the ideology of English landscape gardening in the age of romanticism. On the other hand the phenomenon is compared with the theories of aestheticism, as they were discussed at the Vienna university in the middle of l9th century.